Relationship between psychological distress and manifest behaviors of young adults in the Detroit Metro area during a COVID-19 wave - Sehaj Gill (Eximia, 2024)
The COVID-19 pandemic has had unprecedented effects on individuals and societies. While the adverse physical effects of the pandemic are apparent, the mental effects are arguably more prevalent and long lasting. The body of knowledge, especially for younger populations needs to be expanded. Using a survey instrument based on Depression Anxiety Stress Scale-21 and C.S Mott Children’s Hospital National Poll, 412 responses were collected between January 19, 2022, and February 7, 2022, from people between ages 18 to 25 in the Detroit Metro area. Analysis of Variance (ANOVA), Kruskal-Wallis and Chi-Square tests of the collected data suggest depression, anxiety, and stress manifested as specific detrimental behaviors in young people at a 95.0% confidence level. Specifically, ANOVA suggested that depression was associated with manifest behaviors of worry, sadness, changes in appetite and withdrawing from friends and family. Anxiety was associated with sleep issues. Stress was associated with worry, sadness, and aggressive behavior. These results could offer guidance on which manifest behaviors can be addressed to possibly alleviate specific dimensions of psychological distress. In situations where response windows are short and/or where the resources are limited, policy makers and caregivers can prioritize treating and addressing these manifest behaviors.